Pulmonary sarcoidosis: a case report with typical imaging features - Ahmad, Kaleem; Rauniyar, RK; Ansari, S; Dhungel, K; Gupta, MK; Sah, PL; Pant, AR (Health Renaissance, 2013)
Sarcoidosis is a granulomatous disorder multisystem involvement; however, pulmonary manifestations typically dominate with abnormal chest radiographs in majority of the patients. Pulmonary function tests like vital capacity and total lung capacity are reduced. The typical radiographic feature of sarcoidosis is bilateral hilar lymphadenopathy with involvement of right paratracheal lymph nodes concomitantly. Computed tomographic scan is ahead of conventional chest radiographs in depicting parenchymal, mediastinal and hilar abnormalities. Transbronchial lung biopsy and transbronchial needle aspiration are important for diagnosing pulmonary sarcoidosis. Health Renaissance, January-April 2013; Vol. 11 No.1; 169-171 DOI: http://dx.doi.org/10.3126/hren.v11i2.8228